Bio-inspired drag reduction: From nature organisms to artificial functional surfaces. (June 2020) - Yu, Cunming; Liu, Mengfei; Zhang, Chunhui; Yan, Hao; Zhang, Minghui; Wu, Qingshan; Liu, Mingjie; Jiang, Lei
Highlights: Owing to the increasing global energy crisis, drag reduction, which can efficiently lower the energy consumption in the fields of marine vehicles, aircraft, pipeline transportation, microfluidics, and so on, has attracted wide attentions from fundamental researches and practical applications. Nature organisms in billions of years of evolution have evolved elegant morphologies, structures, patterns, or surface wettabilities, which have endowed them with unique drag reduction abilities. According to their unique mechanisms and high adaptabilities, we would like to introduce five kinds of well-known natural examples in the field of drag reduction: the shark skin-inspired drag reduction, the dolphin skin-inspired drag reduction, the penguin-inspired microbubble drag reduction, the lotus leaf-inspired superhydrophobic drag reduction, and the pitcher plant-inspired slippery drag reduction. In this nature organisms-oriented review, we will discuss the mechanisms of natural drag reduction and how they were explored. Then, the corresponding biomimetic strategies for drag reduction will be introduced to show how these biological drag reduction strategies can be translated from nature to artificial functional surfaces. Also, the advantages and drawbacks for each individual example will be simply concluded. Finally, the remaining challenges and future outlook of drag reduction are briefly addressed. Abstract: Nature organisms, after billions of years of evolution, have evolved elegant morphologies, structures, patterns, or surface wettabilities with unique functionalities. Among all the intriguing characteristics observed in nature organisms, their drag reduction abilities with low energy consumption have always attracted wide attentions of human beings, because of its great potentiality in various fields, e.g., marine vehicles, aircraft, pipeline transportation, microfluidics, etc. Recently, in-depth studies have been carried out to uncover various biological structures with distinguished drag reduction performance including shark skins, penguin feathers, dolphin skins, lotus leaves, and Nepenthes pitcher. In this review, we will give a succinct account of their drag-reduction mechanisms as well as introduce the recent biomimetic processes to create artificial drag-reduction surfaces. Meanwhile, the remaining challenges and future prospective of bio-inspired drag reduction are also briefly proposed. We hope this review can help people to learn about the natural wisdoms to reduce fluid resistance and stimulate people to develop efficient drag reduction approaches, which are essential for submarine and cargo ship navigation, air vehicles, pipeline transportation, microfluidic system, and so forth. Graphical abstract: Image, graphical abstract